PENGARUH AUDIT TENURE TERHADAP FRAUDULENT FINANCIAL REPORTING DENGAN PENDEKATAN AKRUAL DISKRESIONER - Nur apandi, R. Nelly (Jurnal Riset Akuntansi dan Keuangan, 2013)
The purpose of this research was to describe audit tenure, fraudulent fianncial repoting, and the effect audit tenure on fraudulent fianncial reporting with discretionary accrual approach. This research used 83 samples of companies listed in Indonesia Stock Exchange period 2009-2010. Samples was collected by used puposive sample method. The hypothesis tested by simple linear regression analysis. The results of this study indicate that audit tenure for three consecutive years (2009-2011) there were 16 companies that have changed auditors every year, 36 companies that perform audit engagements with the same auditor for 2 years, and 31 companies that perform audit engagements with the same auditor for 3 years.While, the results of descriptive analysis showed that the fraudulent financial reporting has a minimum value is -0.7940, maximum values is 0.3670, and an average of fraudulent financial reporting at 83 companies listed in the Indonesia Stock Exchange is -0.010622. Financial reporting fraud rate indicates a value of less than zero (-0.010622), which indicates that there are indications of fraud in the form of earnings management with minimazation income, which lowers the level of income reported earnings. The results of hypothesis showed that the audit tenure has no effect on fraudulent financial reporting.